Implementation of NodeMCU ESP8266 Microcontroller for Teacher Attendance System at SMK Swasta Pemda Rantauprapat - Mulia, Ahmad; Subagio, S; Ritonga, Wahyu Azhar (U-NET Jurnal Teknik Informatika, 2024)
NodeMCU is an open source IoT platform, NodeMCU ESP8266 can be used for Internet of Things (IOT) because the facilities are equipped with Wi-Fi, RFID is a process of identifying objects or objects using radio frequency, this device is widely sold in stores online at a very low price. The type of research used in this research is qualitative research, while the data collection method used is observation andto study, the design method uses the method postage type. This system tests every piece of hardware used and tests the software from a specific functional perspective. The result of this study is the teacher attendance system using Microcontroller NodeMCU ESP8266 replace the manual attendance recording model in the attendance book by writing the entry and rturn hours and filling in the teacher's signature with id card attached to the device RFID connected to microcontroller NodeMCU ESP8266. Thus, reducing the occurrence human error when recap attendance, and reduce paper use.